BNTA alleviates inflammatory osteolysis by the SOD mediated anti-oxidation and anti-inflammation effect on inhibiting osteoclastogenesis - Wang, Huidong; Cao, Xiankun; Guo, Jiadong; Yang, Xiao; Sun, Xiaojiang; Fu, Zhiyi; Qin, An; Wu, Yujie; Zhao, Jie (Frontiers in Pharmacology, 2022)
Abnormal activation and overproliferation of osteoclast in inflammatory bone diseases lead to osteolysis and bone mass loss. Although current pharmacological treatments have made extensive advances, limitations still exist. N-[2-bromo-4-(phenylsulfonyl)-3-thienyl]-2-chlorobenzamide (BNTA) is an artificially synthesized molecule compound that has antioxidant and anti-inflammatory properties. In this study, we presented that BNTA can suppress intracellular ROS levels through increasing ROS scavenging enzymes SOD1 and SOD2, subsequently attenuating the MARK signaling pathway and the transcription of NFATc1, leading to the inhibition of osteoclast formation and osteolytic resorption. Moreover, the results also showed an obvious restrained effect of BNTA on RANKL-stimulated proinflammatory cytokines, which indirectly mediated osteoclastogenesis. In line with the in vitro results, BNTA protected LPS-induced severe bone loss in vivo by enhancing scavenging enzymes, reducing proinflammatory cytokines, and decreasing osteoclast formation. Taken together, all of the results demonstrate that BNTA effectively represses oxidation, regulates inflammatory activity, and inhibits osteolytic bone resorption, and it may be a potential and exploitable drug to prevent inflammatory osteolytic bone diseases.